Pendekatan Case Work dalam Pemulihan Psikologis Anak Berhadapan dengan Hukum di UPTD PPA Kota Medan - Angelia Febrianne; Fajar Utama Ritonga; Berlianti B (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study examines the role of QR Code-based ordering systems in improving service quality and operational efficiency in Food and Beverage (FB) Micro, Small, and Medium Enterprises (MSMEs), using Mie Gacoan as a case study. The research employs a qualitative approach through a systematic literature review of six relevant studies published between 2022 and 2025. The findings indicate that QR Code-based ordering systems reduce customer waiting times, minimize order recording errors, and enhance employee productivity by streamlining the ordering process. In terms of service quality, the technology supports key SERVQUAL dimensions, including responsiveness, reliability, and tangibles, while improving overall customer experience. Furthermore, the system contributes to more efficient operational workflows and better resource utilization. Despite these benefits, challenges such as varying levels of digital literacy and initial technology investment remain important considerations. This study provides insights into the potential of digital ordering systems to support service and operational improvements in FB MSMEs.